1976
DOI: 10.1159/000301395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gestational Age, Dexamethasone, and Metopirone on Lecithin Concentration in Fetal Lung Tissue and Amniotic Fluid in Rats and Guinea Pigs

Abstract: There is a significant increase in acetone-precipitable lecithin (APL) concentration with advancing gestation in fetal lung tissue and amniotic fluid in rats. Measurement of the APL concentration in fetal lung tissue and/or amniotic fluid provides an excellent model for evaluation of fetal lung maturation. The surge of lecithin concentration in amniotic fluid lags behind that in fetal lungs by about 1 day. This supports the concept that fetal lungs are a main contributor to the amniotic fluid lecithin pool. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The significant decreases in lung tissue DSPC and DSPCITPL we demonstrated during the final 2 days of gestation, following maternal metyrapone treatment in the rat are in agreement with earlier studies with this agent showing altered surfactant levels or function in rabbits (IS), baboons (12), and guinea pigs (14). Our study, in addition, has demonstrated for the first time a parallel delay following metyrapone in a nonsurfactant-related biochemical system in fetal lung, the antioxidant enzyme system.…”
Section: Discussionsupporting
confidence: 92%
“…The significant decreases in lung tissue DSPC and DSPCITPL we demonstrated during the final 2 days of gestation, following maternal metyrapone treatment in the rat are in agreement with earlier studies with this agent showing altered surfactant levels or function in rabbits (IS), baboons (12), and guinea pigs (14). Our study, in addition, has demonstrated for the first time a parallel delay following metyrapone in a nonsurfactant-related biochemical system in fetal lung, the antioxidant enzyme system.…”
Section: Discussionsupporting
confidence: 92%
“…Metopirone, an inhibitor of cortisol synthesis, has been reported to delay lung maturation in the fetal rabbit (222), rat (164) and guinea pig (164). Glucocorticoids are used clinically in the prevention of RDS in human infants (14,16,170), although there is controversy that such use may have deleterious effects on the development of other organs (223)(224)(225)(226)(227).…”
Section: Glucocorticoidsmentioning
confidence: 99%